METODE PELATIHAN ANGKLUNG PADA ANAK USIA 6-12 TAHUN DI GEREJA PANTEKOSTA DI INDONESIA SILOAM SALATIGA - Petra Krisetya Martini; Feritrio Harmony; Daniel Sema (STT Kristus Alfa Omega, 2021)
At the Pantecostal Church in Indonesia â€œSiloamâ€, Salatiga, there are 6-12 years old children that play angklung music instruments cohesively. In this research the writer tries to find the method used to train 6-12 years old children by observising the process of angklung training for children at the Pantecostal Church in Indonesia â€œSiloamâ€, Salatiga.In the research the writer uses qualitative research method. In the qualitative research method, the writer becomes the key of instrument. To know the method training used in the angklung training for 6-12 years old childern at the Pantecostal Church in Indonesia â€œSiloamâ€, Salatiga, the writer needs to observe angklung training directly. Besides, the data finding is done by recording, photographing, and interviewing. The data become the materials to be analized. Before analyzing the data the writer studies the concepts, literature, and books related to the research.The conclusion of the research is that the success of angklung learning can be achived if the children are trained continously. If the angklung trainer applies proper method and continous training, the children are able to study angklung instrument successfully.